Evaluating The Effectiveness of Indonesia-Iom Cooperation in The Governance of Human Trafficking and Illegal Labor Migration - Aqnisyah, Devara Izzatun; Azmawati , Dian (Universitas Muhammadiyah Yogyakarta, 2023)
Human trafficking and illegal labor migration are forms of modern slavery that have been an International issue that indeed violates activity of human rights, and inflicts threat to national and human security. The rapid development of its issue needs international cooperation which conducted by international organizations and involved countries, such as Indonesia-IOM (International Organization for Migration). Indonesia is a country that receives, sends, and transits country of human trafficking activities, whereas IOM is an international organization that has the authority to assist the issue by cooperations. The cooperation is taken to reduce the number of cases and also handle human trafficking and illegal labor migration. Indonesia-IOM cooperation has generated efforts categorized as; (1) identify and enforce the law; (2) regulate immigration and providing assistance; (3) prevention in the form of training/socialization. The result of this cooperation has impacted Indonesia's placement in tier 2 as a country that attempts to handle human trafficking and illegal labor migration although it is not yet in accordance with the standards of handling Trafficking in Persons